Breaking the Dahi Handi - Mumbai Archive Project Team (Jio Institute, 2024)
During the Dahi Handi event outside the Ram Mandir, the handi (pot) is not broken by forming a human pyramid; instead, it is broken by bamboo spears. As a safety measure, the pot is placed in a netted bag to prevent injuries from falling shards.